Digital avionics handbook - Spitzer, Cary R.; Ferrell, Uma; Ferrell, Thomas; Abbott, Kathy H. (CRC Press, 2015)
A perennial bestseller, the Digital Avionics Handbook offers a comprehensive view of avionics. Complete with case studies of avionics architectures as well as examples of modern systems flying on current military and civil aircraft, this Third Edition includes:Ten brand-new chapters covering new topics and emerging trendsSignificant restructuring to deliver a more coherent and cohesive storyUpdates to all existing chapters to reflect the latest software and technologiesFeaturing discussions of new data bus and display concepts involving retina scanning, speech interaction, and synthetic vision.